Activation of persulfate by manganese oxide-modified sludge-derived biochar to degrade Orange G in aqueous solution - Zixi Fan; Qian Zhang; Meng Li; Wenjiao Sang; Yue Qiu; Chenfeiyang Xie (Environmental Pollutants & Bioavailability, 2019)
Manganese oxide-loaded sludge-derived biochar (Mn-SDBC) was synthesized and used to activate persulfate (PS) for Orange G (OG) degradation. X-ray fluorescence and Fourier transform infrared spectroscopy analysis indicated that the manganese oxides were successfully loaded on the SDBC. The result of batch experiments suggests that OG can be efficiently degraded by PS activated by Mn-SDBC. Metal loading rate, biochar dosage and PS concentration play a crucial role in experiments, whereas pH has a minor effect on OG removal. The free radical quenching experiment was investigated to determine the predominant radical species, and the activation mechanism was also illustrated. The as-synthesized Mn-SDBC can efficiently activate PS and removal OG under a continuous flow condition in a fixed-bed column. Our study suggests that Mn-SDBC would be a promising catalyst for the remediation of dye-contaminated wastewater.